2014
DOI: 10.1140/epjc/s10052-014-3051-8
|View full text |Cite
|
Sign up to set email alerts
|

Superradiant instability of charged scalar field in stringy black hole mirror system

Abstract: It has been shown that the mass of a charged scalar field in the background of a charged stringy black hole is never able to generate a potential well outside the event horizon to trap the superradiant modes. This is to say that the charged stringy black hole is stable against massive charged scalar perturbations. In this paper we will study the superradiant instability of the massless scalar field in the background of charged stringy black hole due to a mirror-like boundary condition. The analytical expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 50 publications
2
51
0
Order By: Relevance
“…Clearly, when the charge of scalar field increases, this critical radius decreases correspondingly. This point has also been observed in [40] where the analytical calculation was present. From the analytical result (9), one can obtain that the critical radius can be approximately given by…”
supporting
confidence: 73%
“…Clearly, when the charge of scalar field increases, this critical radius decreases correspondingly. This point has also been observed in [40] where the analytical calculation was present. From the analytical result (9), one can obtain that the critical radius can be approximately given by…”
supporting
confidence: 73%
“…(35) in Ref. [25], one can obtain the mirror radius that supports the scalar cloud; it can be approximately given by…”
Section: Numerical Procedures and Resultsmentioning
confidence: 99%
“…To generate the superradiant instability [21,22], the mirror-like boundary condition should be imposed according to the black hole bomb mechanism [23,24]. Analytical and numerical studies of this subject can be found in [25] and [26]. Correspondingly, the scalar clouds are only possible with the mirror-like boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to remark that we have another possibility to study the accretion process for this metric, which is by taking A 2 < 0 and using (32) and (33) with a minus of difference. In that case we have ρ > 0 for w > −1 as we required, but u(r ) < 0 for w < −1.…”
Section: Spherically Symmetric Metrics With Horizonsmentioning
confidence: 99%